2009
DOI: 10.1016/j.cbpa.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, ventilatory and hygric physiology of the chuditch (Dasyurus geoffroii; Marsupialia, Dasyuridae)

Abstract: The chuditch is a large carnivorous dasyurid marsupial. Historically it had one of the widest geographical distributions of all marsupials, encompassing much of arid Australia, but it is now restricted to the mesic south-west of Western Australia. It is therefore of interest to determine if its physiology better reflects adaptation to its historically arid or present mesic habitat. The basic physiological parameters of the chuditch conform to other marsupials.Body mass of males (1385g) at an ambient temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…This pattern of T b consistency at lower T p 35Њ a T a and then hyperthermia at high T a is expected for a euthermic mammal (e.g., McNab 1980;Withers 1992) and is consistent with that observed for other species of dasyurid marsupial (e.g., Robinson and Morrison 1957;Nicol and Maskrey 1980;Dawson and Dawson 1982;Geiser 1986;Schmidt et al 2009;Cooper and Withers 2010). Many smaller dasyurid species are relatively thermolabile at low T a (Morton and Lee 1978;Dawson and Wolfers 1978;Withers andCooper 2009a, 2009b;Warnecke et al 2010), but dibblers maintained a constant T b below thermoneutrality and showed no tendency for torpor during experiments.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…This pattern of T b consistency at lower T p 35Њ a T a and then hyperthermia at high T a is expected for a euthermic mammal (e.g., McNab 1980;Withers 1992) and is consistent with that observed for other species of dasyurid marsupial (e.g., Robinson and Morrison 1957;Nicol and Maskrey 1980;Dawson and Dawson 1982;Geiser 1986;Schmidt et al 2009;Cooper and Withers 2010). Many smaller dasyurid species are relatively thermolabile at low T a (Morton and Lee 1978;Dawson and Wolfers 1978;Withers andCooper 2009a, 2009b;Warnecke et al 2010), but dibblers maintained a constant T b below thermoneutrality and showed no tendency for torpor during experiments.…”
Section: Discussionsupporting
confidence: 62%
“…35Њ a This is the expected pattern from the Scholander-Irving model for an endotherm (e.g., McNab 1980;Withers 1992), reflecting the increased metabolic heat production required for thermoregulation of a constant T b at low T a , and it is typical of normothermic dasyurid marsupials (e.g., Nicol and Maskrey 1980;Geiser 1986;MacMillen and Dawson 1986;Schmidt et al 2009;Withers andCooper 2009a, 2009b;Cooper and Withers 2010;Warnecke et al 2010). The predicted T b from the relationship of Vo 2 with T a below thermoneutrality of 36.2ЊC was very similar to the measured T b (36.3ЊC), confirming the near conformity of dibblers to the Scholander-Irving model.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations